Infringement Of Trade Marks Under The Trade Marks Act 1976 - Tay, Pek San (Journal of Malaysian and Comparative Law, 2019)
Trade marks have long been used by traders to denote the origin of their products thereby enabling customers to identify these products and distinguish them from products made or sold by others. Today, trade marks also play the additional role of quality indicator in that they suggest to customers that products with the same mark are of consistent quality and similar to the one previously purchased, experienced or portrayed. In this free market economy characterised by an overabundance of products and imbalance of access to accurate information, trade marks aid customers in their choice and encourage competition on the part of traders and manufacturers.